Analysis Of Social Media Marketing Strategies And Markerting Mix In Coffee Shop Business Design Blok18 On Purchase Decisions - Anggoro, Deni; Hasin, Al (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to design a business development strategy for Coffee Shop Blok18, a creative coffee shop in Tegal City that carries the concept of creative urban by combining elements of art, community, and customer experience in one space. This study uses a comprehensive analysis approach that includes SWOT, Value Proposition Canvas, Business Model Canvas, and Marketing Mix (7P) to identify strengths, weaknesses, opportunities, and threats, and to develop strategies that are relevant to market needs and business uniqueness. The results of the analysis show that Coffee Shop Blok18 has strengths in its unique creative concept, loyal customer community, and distinctive coffee shop atmosphere. However, there are weaknesses in aspects of similar competition in the coffee shop industry, service efficiency and product diversification. Great opportunities are open through the trend of drinking coffee among young people, the growth of local creative communities, and the potential for digitalization of services. Threats that need to be anticipated include tight competition in the coffee shop industry and fluctuations in raw material prices. The resulting strategy recommendations include strengthening the value proposition through trend-based product innovation, increasing service efficiency with a pre-order system and digitalization of ordering, and strengthening marketing channels through social media and community collaboration. In addition, business expansion strategies and development of customer experience-oriented business models are also formulated to ensure sustainability and long-term growth.